An fMRI study of multi-modal semantic and phonological processing in reading disabled adolescents - Landi, Nicole (2010)
Using fMRI we investigated multimodal (visual and auditory) semantic and unimodal (visual only) phonological processing in reading disabled (RD) adolescents and non-impaired (NI) control participants. We found reduced activation for RD relative to NI in a number of left-hemisphere reading-related areas across all processing tasks regardless of task type (semantic vs. phonological) or modality (auditory vs. visual modality). Moreover, activation differences in these regions, which included the inferior frontal gyrus (IFG), the superior temporal gyrus (STG) and the occipitotemporal region (OT), was largely independent of in-scanner performance in our auditory semantic task. That is, although RD participants and NI participants differed in performance in visually presented conditions, they did not differ significantly in the auditory condition, yet similar patterns of reduced activation were observed in these regions across conditions. These findings indicate a neurobiological marker in RD that is independent of task, modality or performance. These findings are discussed in the context of current neurobiological models of RD.